Developmental regulation of a sporulation-specific enzyme activity in Saccharomyces cerevisiae. - Clancy, M J (1982)
An alpha-glucosidase activity (SAG) occurs in a/alpha Saccharomyces cerevisiae cells beginning at about 8 to 10 h after the initiation of sporulation. This enzyme is responsible for the rapid degradation of intracellular glycogen which follows the completion of meiosis in these cells. SAG differs from similar activities present in vegetative cells and appears to be a sporulation-specific enzyme. Cells arrested at various stages in sporulation (DNA replication, recombination, meiosis I, and meiosis II) were examined for SAG activity; the results show that SAG appearance depends on DNA synthesis and some recombination events but not on the meiotic divisions.